Female Consumers' Interest in Eco-Packaging of Cosmetic Products in Poland - Iga LAMAR (Communications of International Proceedings, 2021)
The main objective of this paper is to evaluate consumers’ interest in eco-packaging of cosmetic products. As majority of respondents (over 96%) are women, this phenomenon and research results will consider solely female consumers. The research using indirect method of communication with consumers was based on the online questionnaire survey. The research was conducted among 275 Polish respondents. The research results show that consumers have knowledge about eco-packaging in a form of recycled plastic or glass. More innovative solutions such as plant-based packaging are still not well-known. Those who know plant-based packaging are mostly young, well-educated women. The research results underline a strong relation between education and awareness of latest innovations in the eco-packaging industry. The small number of men participating in the survey does not allow to discuss the phenomenon among them.
Keywords: Ecological consumer behaviour; cosmetic packaging; eco-packaging; Polish consumers